Long-term impact of diabetes on mortality in patients undergoing unprotected left main PCI: a propensity score-matched analysis from the BIA-LM registry - Paweł Kralisz; Emil Julian Dąbrowski; Sławomir Dobrzycki; Wiktoria Urszula Kozłowska; Patrycja Oliwia Lipska; Konrad Nowak; Kamil Gugała; Przemysław Prokopczuk; Grzegorz Mężyński; Michał Święczkowski; Marcin Kożuch (Cardiovascular Diabetology)
Abstract Background There is modest data on long-term impact of diabetes on left main coronary artery (LMCA) percutaneous coronary intervention (PCI). This observational study, based on the largest single-center registry of LMCA PCI in Poland, evaluated the impact of diabetes on long-term survival following PCI in a real-world setting. Methods We retrospectively analyzed 998 patients who underwent LMCA PCI between December 27, 2007, and February 21, 2022. Diabetes and insulin dependence were defined based on medical history, prior records, and prescribed treatment. The endpoint was all-cause mortality at the longest available follow-up (mean 4.2 years). Survival analysis was conducted in the overall cohort and a one-to-one propensity score-matched (PSM) population. Moderation effects and differences between subgroups were analysed in predefined groups of PSM cohort. Results The median age was 71 (63–79) years; 212 (28.2%) were women, and 250 (33.2%) had diabetes. In the overall cohort, diabetes was associated with a worse prognosis (HR 1.35, 95% CI 1.03–1.76, P = 0.03). PSM resulted in 214 well-balanced pairs (median age 73 years (66–79)), with no significant difference in all-cause mortality between groups (adjusted HR 1.27, 95% CI 0.91–1.77, P = 0.16). After PSM subgroup analysis showed worse outcomes for patients with diabetes undergoing two-stent angioplasty (HR 3.70, 95% CI 1.64–8.34, P = 0.002) and elective PCI (HR 2.07, 95% CI 1.29–3.31, P = 0.003). Conversely, among patients presenting with myocardial infarction (MI), people with diabetes had better survival than the control group (HR 0.56, 95% CI 0.35–0.90, P = 0.02). No significant differences in outcomes were observed in patients with heart failure (HR 1.29, 95% CI 0.88–1.89, P = 0.19), chronic kidney disease (HR 1.08, 95% CI 0.69–1.71, P = 0.19), intravascular imaging use (HR 1.38, 95% CI 0.70–2.71, P = 0.35), or concomitant multivessel disease (HR 1.14, 95% CI 0.75–1.73, P = 0.53). Conclusions No significant association was observed between diabetes and overall mortality following LMCA PCI. Sensitivity analyses showed worse survival outcomes in diabetic patients treated with two-stent techniques and undergoing non-emergency PCI. These findings suggest the overall safety of PCI for LMCA in people with diabetes and highlight the need for randomized trials, especially investigating indicated high-risk subgroups. Graphic abstract